Cloning and expression of recombinant human platelet-derived growth factor-BB in Pichia Pink - Babavalian, H; Latifi, A M; Shokrgozar, M A; Bonakdar, S; Tebyanian, H; Shakeri, F (Cellular and Molecular Biology, 2016)
The PDGF-BB plays a key role in several pathogenesis diseases and it is believed to be an important mediator for wound healing. The recombinant human PDGF-BB is safe and effective to stimulate the healing of chronic, full thickness and lower extremity diabetic neurotrophic ulcers. In the present study, we attempted to produce a PDGF-BB growth factor and also, evaluate its functionality in cell proliferation in yeast host Pichia pink. Pichia pink yeast was used as a host for evaluation of the rhPDGF-BB expression. The coding sequence of PDGF-BB protein was synthesized after optimization and packed into the pGEM. Recombinant proteins were produced and purified. The construct of pPinkÎ±-HC-pdgf was confirmed by sequence, the PDGF-BB protein was expressed and purified with using a nickel affinity chromatography column and then characterized by SDS-PAGE electrophoresis. The biological activity of PDGF-BB was estimated with using human fibroblast cell line. The measurement of protein concentration was determined by Bradford and human PDGF-BB ELISA kit. Purified rhPDGF-BB showed similar biological activity (as the standard PDGF-BB) and suggested that the recombinant protein has a successful protein expression (as well as considerable biological activity in P. pink host). The exact amount of recombinant PDGF-BB concentrations were measured by specific ELISA test which it was about 30 g/ml. Our study suggested that efficiency of biological activity of PDGF-BB protein may be related to its conformational similarity with standard type and also, it practically may be important in wound healing and tissue regeneration.